Estudo da 1º lei de ohm nas associações de resistores através de simulador no scratch, aplicada em turmas de 3º ano do ensino médio - Castro, Hamilton José Duarte de (2019)
This work is an integral part of the curriculum for completing the course of the national professional master's degree in physics teaching and refers to the use of a new technology called SCRATCH to improve the methodology of physics teaching in institutions that do not have didactic physics laboratories or where. It will be specifically addressed the subject of electricity (electric circuits), seeking to show specifications of the electrical circuits in series, in parallel and mixed, identifying the relation of the electric quantities of the 1st Law of Ohm. Through a simulator in which the student himself has the possibility to assemble his circuit and discover the various situations during the assembly. The work presented is a playful deferent of showing the operation of electrical circuit equipment’s. The educational product was tested in the high school Professor Flávio Ponte, with students of the 3rd year of the night shift, in which the methodology was the application of a pre-test to analyze the previous knowledge of the students, soon after the intervention was made in the classes and finally a post-test was applied to identify the growth of students' cognitive knowledge in relation to the subject addressed. We came to the conclusion that the production of knowledge made through visual and auditory stimuli causes the student to have a more meaningful learning of the content addressed